EVALUASI KINERJA DOSEN UNTUK PENENTUAN DOSEN TELADAN MENGGUNAKAN METODE MULTI FACTOR EVALUATION PROCESS (MFEP) - Zulmi; Afianto, Dafit (Jurnal Informatika Medis, 2025)
This study aims to propose a lecturer performance evaluation model based on a Decision Support System using the Multi Factor Evaluation Process (MFEP) method, tailored to the Tri Dharma of Higher Education framework in regional private universities. Unlike conventional evaluation approaches that tend to be subjective, the proposed model integrates systematic criterion weighting and multi-criteria assessment to enhance objectivity and decision consistency. The evaluation criteria include teaching, research, community service, scientific publications, and discipline. The research data were collected from 13 lecturers of the Primary School Teacher Education Study Program over one academic year. The results indicate that the MFEP method is able to generate a measurable and transparent ranking of lecturer performance. This study provides a practical contribution in the form of a contextual and applicable lecturer performance evaluation model to support institutional decision-making in regional private higher education institutions.